Increasing Self-Esteem to Attract and Retain Farmers in Agriculture Profession - Nath , Sujit K. (Indian Journal of Extension Education, 2022)
Besides income, prestige also plays a major role in selection of profession. Lowering of self-\ esteem is perceived as one of the major setbacks for reducing attraction towards farming by the current generation. Krishi Vigyan Kendra, Deogarh, Odisha developed a strategy and worked upon it during 2018-19 and 2019-20 to increase the social status of farmers by increasing their human values. The selected farmers were branded as experts in certain fields before a public gathering. Their role and success story was highlighted through different mass media. The effect of such action was observed and recorded. The branded farmers felt their increased social status after branding by KVK. These young farmers served as a medium for technology transfer in their locality. Increasing of self-esteem was perceived as the greatest effect of branding by the farmers. The studied farmers were of the opinion that even after recognized by government, they had the least opportunity to easily avail government schemes. This novel approach was found a successful step towards encouraging farmers, rural agripreneurs as well as transfer of farm technologies. The model can be replicated successfully in agriculture and other such areas for a wholesome development.
Keywords: Agriculture, Brand; KVK; Model; Perception; Self-esteem